Religius Obligation dan Social Influence Terhadap Keputusan Muslim Generasi Z Untuk Menabung di Bank Syariah (Studi Pada Muslim Generasi Z di Kabupaten Jepara) - Naili Rahma Yuliani; Miswan Ansori (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to address whether religious obligation and social influence affect the decision to save in Islamic banks among Muslim Generation Z in Jepara Regency. The research employs a quantitative approach with primary data collected through online questionnaires. A purposive sampling method was used to select 96 respondents. The analytical technique applied is multiple linear regression. The findings indicate that both religious obligation and social influence have a significant impact on the decision to save in Sharia banks. Interestingly, social influence has a greater impact compared to religious obligation in shaping this decision. These findings highlight the importance of community and social norms in shaping Generation Z's financial behavior when choosing financial institutions for saving and provide valuable insights for Sharia banks to develop more effective marketing strategies